Answer: A & B
Step-by-step explanation:
Answer:
Square both sides and then solves the resulting quadratic equations
Step-by-step explanation:
The equation is 3sqrt(x^2-6)=3sqrt(2x+2)
We can solve this by;
First square both sides;
(3√(x²-6))²= (3√(2x+2))²
We obtain;
9(x²-6)=9(2x+2)
We simplify to obtain a quadratic equation;
x²-6=2x+2
= x²-2x-8=0
Then we solve the quadratic equation;
x²-4x+2x-8=0
x(x-4)+2(x-8)=0
(x+2)(x-8)=0
Values of x = -2 or 8
Answer:
Cube both sides and then solve the resulting quadratic equation.
Step-by-step explanation:
It's the answer on edge